2015
DOI: 10.2174/1381612821666150531170448
|View full text |Cite
|
Sign up to set email alerts
|

Zein-Based Nanofibres for Drug Delivery: Classes and Current Applications

Abstract: Plant proteins have been drawing increasing attention owing to their safety, abundance and relatively low cost in comparison with animal proteins. The development of plant protein-based delivery vehicles may lead to the provision of novel pharmaceutical products to patients. Zein is a class of alcohol-soluble prolamine proteins present in maize endosperm that was approved as a generally recognised as safe excipient in 1985 by the US FDA for use in pharmaceutical film coatings. Over the past few decades, numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…1 Among these, zein and zein-based carriers have drawn much attention from experts in both food and pharmaceutical fields due to its molecular characterization, cytocompatibility, and biodegradability. [2][3][4][5] Zein belongs to the class of prolamin proteins and is the main storage protein of maize. Zein is primarily present as protein bodies in endosperm cells and can be extracted and separated with various technologies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Among these, zein and zein-based carriers have drawn much attention from experts in both food and pharmaceutical fields due to its molecular characterization, cytocompatibility, and biodegradability. [2][3][4][5] Zein belongs to the class of prolamin proteins and is the main storage protein of maize. Zein is primarily present as protein bodies in endosperm cells and can be extracted and separated with various technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial zein usually refers to α-zein with a purity higher than 90%. Numerous studies have demonstrated that zein could be fabricated into various carriers, such as films, 3 nanofibers, 4 nano/microparticles, 8 nano/microcapsules, 9,10 and micelles. 11 These carriers and their biomedical applications have been reviewed recently.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main plant proteins is the corn prolamin protein called zein [ 6 , 7 ]. Zein, the major storage protein in the endosperm of corn, is classified into three different fractions, based on differences in solubility and molar mass: α-, β- and γ-zein [ 8 ]. It has been shown to be resistant to microbial attacks, it has low toxicity, is biologically compatible, biodegradable, renewable and FDA approved as one of the recognized, safe excipients for film coatings of pharmaceuticals [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%